The Idea of a Global History of Philosophy - Skirbekk, Gunnar (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
In this paper I assume, by definition, that philosophers are arguing, first and foremost concerning their own validity claims, but now and then also concerning claims or presuppositions presented by other thinkers, and also concerning validity claims raised by scientists and scholars in different fields, or concerning political ideologies or religious claims, or concerning major events and challenges in societies. Hence, a history of philosophy should be situated and argumentative: both socio-historically situated, and argumentative, taking various validity claims seriously. Hence, we could learn something from these thinkers, and not merely about them. Moreover, for a global history of philosophy, in our time, it should be brought up to our present situation, epistemically and otherwise. If so, the idea of a global history of philosophy, conceived in this way, tends to become a history of global modernization – certainly, each time with its short-comings and special selections.